Hubungan Aktivitas Pengunaan Gadget Terhadap Kejadian Miopia Pada Mahasiswa Fakultas Kedokteran Universitas Palangka Raya - Hertanto, Bima Adithya; Martani, Natalia Sri; Adnyana, I Gde Hary Eka; Manalu, Rosmaryati; Augustina , Indria (Jurnal Kedokteran Universitas Palangka Raya, 2025)
Technological advancements, particularly gadget use, offer benefits but increase myopia risk. Myopia prevalence is rising globally, including in Indonesia, especially among adolescents and young adults. Factors like viewing distance, usage duration, room light intensity, screen brightness, and posture contribute to this trend. This study aims to determine the relationship between gadget usage and myopia among students of the Faculty of Medicine, Universitas Palangka Raya, Class of 2023. A cross-sectional study was conducted with 85 respondents. Data were collected via questionnaires and eye examinations, analyzed using Spearman’s correlation test. Significant relationships were found between usage duration, room light intensity, screen brightness, and viewing distance with myopia. Posture during gadget use showed no significant relationship. Gadget usage activities are significantly associated with myopia incidence among respondents.